2006
DOI: 10.1002/art.22244
|View full text |Cite
|
Sign up to set email alerts
|

Course of functional status and pain in osteoarthritis of the hip or knee: A systematic review of the literature

Abstract: Objective. To systematically review studies describing the course of functioning in patients with osteoarthritis (OA) of the hip or knee and identifying potential prognostic factors. Methods. A systematic search was performed. Studies involving patients with hip or knee OA, >6 months of followup, and outcome measures on functional status or pain were included. Methodologic quality was assessed using a standardized set of 11 criteria; a qualitative data analysis was performed.Results. Approximately 6,500 titles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
3
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 221 publications
(167 citation statements)
references
References 36 publications
9
150
3
5
Order By: Relevance
“…wiley.com/journal/10.1002/(ISSN)2151-4658); this was adapted for EMBase, CINAHL, AMED, and Web of Science. Reference lists of identified reviews were mined for further studies (5)(6)(7). Neither study type nor language was limited (10,13).…”
Section: Methodsmentioning
confidence: 99%
“…wiley.com/journal/10.1002/(ISSN)2151-4658); this was adapted for EMBase, CINAHL, AMED, and Web of Science. Reference lists of identified reviews were mined for further studies (5)(6)(7). Neither study type nor language was limited (10,13).…”
Section: Methodsmentioning
confidence: 99%
“…Katz et al reported significant differences by sex in functional status before TKA and noted that the differences were not the result of clinical characteristics of the patient, suggesting that patient preferences and access to surgery were possible reasons [7]. van Dijk et al reported no prognostic association between sex and future functional status over 3 years of followup in patients with knee OA [17]. It was reported that physical inactivity was associated with severe joint pain among men but not women [15], suggesting that there may be a complex relationship among activity levels, functional impairment, and pain, which may differ by sex.…”
Section: \0001mentioning
confidence: 99%
“…The benefits of strength training on muscle strength and functional limitations among older people have been confirmed in randomized controlled trials [21,22]. Several well-conducted prospective studies have shown that physical activity protects against the development of chronic conditions such as cardiovascular diseases, arthritis, diabetes, and obesity [23,24], which, in turn, have been shown to be important risk factors for functional limitations [7,25,26].…”
Section: Introductionmentioning
confidence: 91%
“…By the year 2030, about a quarter of the US adult population is projected to suffer from arthritis [44]. With older age, the growing prevalence of chronic diseases such as arthritis accelerates the natural age-related decline in physical functioning [23]. A prospective study using data from the Health and Retirement Study showed that persons who had arthritis at the age of 50 to 62 had a higher risk of developing difficulties in mobility over a 10-year follow-up compared to those who did not suffer from arthritis [35].…”
Section: The Progression Of Functional Limitations and Physical Activmentioning
confidence: 99%
See 1 more Smart Citation